PENGEMBANGAN SPIRITUAL QUOTIENT MAHASISWA MELALUI KULIAH AHAD SUBUH (KAS) : STUDI DI UNIVERSITAS MUHAMMADIYAH MALANG - Ina Sholikhah; Dina Mardiana; Nur Afifah Khurinmaknin (UIN Sumatera Utara Medan, 2024)
This research aims to analyze the spiritual quotient development of Muhammadiyah University of Malang students through the “Kuliah Ahad Subuh” program and analyze the supporting and inhibiting factors in developing the spiritual quotient of Muhammadiyah University of Malang students through this program using theories according to Danah Zohar and Ian Marshall. This research uses a qualitative approach with a study case type of research. The research subjects were students from the University of Muhammadiyah Malang who came from 7 faculties, namely FISIP, FKIP, Law, Engineering, FPP, FEB and Psychology. Data collection methods are carried out through observation, interviews and documentation. Meanwhile, data analysis uses interactive data analysis by Miles, Huberman, and Saldana. The research results showed that students' responses to the “Kuliah Ahad Subuh” program in developing spiritual quotient at the University of Muhammadiyah Malang were in the form of three aspects, namely first self-reflection, second worship, third time discipline and a small number of informants had less response than others in developing spiritual quotient. Supporting factors for developing the spiritual quotient are worship, material things and relationships. Meanwhile, the factors inhibiting the development of the spiritual quotient are provisions on time allocation and self-awareness.